Find $$\lim_{n\to \infty}\frac{(n+1)^\sqrt{n+1}}{n^\sqrt{n}}$$

First I tried by taking $\ln y_n=\ln \frac{(n+1)^\sqrt{n+1}}{n^\sqrt{n}}=\sqrt{n+1}\ln(n+1)-\sqrt{n}\ln(n),$

which dose not seems to take me anywhere. Then I tried to use squeeze theorem, since $\frac{(n+1)^\sqrt{n+1}}{n^\sqrt{n}}\geq 1$, but I need an upper bound now. It's for a while I am trying to come up with it but stuck. Can you help me please.


Notice that for $f(x)=\sqrt x \ln x$ you have $$f'(x)=\frac{\ln x}{2\sqrt x}-\frac1{\sqrt x}.$$ Now by mean value theorem $$f(n+1)-f(n) = f'(\theta_n)$$ for some $\theta_n$ such that $n<\theta_n<n+1$ (by Mean Value Theorem). This means that for $n\to\infty$ we have $\theta_n\to\infty$.

If we notice that $\lim\limits_{x\to\infty} f'(x) = 0$ we get that $$\lim\limits_{n\to\infty} (\sqrt{n+1}\ln(n+1)-\sqrt{n}\ln n) = \lim\limits_{n\to\infty} f'(\theta_n) = 0.$$


Standard trick when things are difficult due to "mixed" terms like this: Write

$$y_n = \sqrt{n + 1} \ln(n + 1) - \sqrt{n} \ln(n + 1) + \sqrt{n} \ln(n + 1) - \sqrt{n} \ln n$$

Now the first two terms can be combined as

\begin{align*} \ln(n + 1) \big(\sqrt{n + 1} - \sqrt{n}\big) &= \ln(n + 1) \frac{1}{\sqrt{n + 1} + \sqrt{n}} \\ &\approx \frac{\ln n}{2\sqrt{n}} \end{align*} which tends to zero via any number of methods. The last two terms are handled similarly, from which you can deduce that the limit of $y_n$ is zero, and the original limit is $1$.


We can do a bit more. Starting with what you wrote $$\ln (y_n)=\ln \frac{(n+1)^\sqrt{n+1}}{n^\sqrt{n}}=\sqrt{n+1}\ln(n+1)-\sqrt{n}\ln(n)$$ rewrite $$\sqrt{n+1}\ln(n+1)=\sqrt n \sqrt{1+\frac 1n}\Big(\ln(n)+\ln(1+\frac 1n)\Big)$$ and now use Taylor series $$\sqrt{1+\frac 1n}=1+\frac{1}{2 n}-\frac{1}{8 n^2}+O\left(\frac{1}{n^3}\right)$$ $$\ln(1+\frac 1n)=\frac{1}{n}-\frac{1}{2 n^2}+O\left(\frac{1}{n^3}\right)$$ which makes $$\sqrt{n+1}\ln(n+1)=\sqrt n \Big( 1+\frac{1}{2 n}-\frac{1}{8 n^2}+O\left(\frac{1}{n^3}\right)\Big)\Big(\ln(n)+\frac{1}{n}-\frac{1}{2 n^2}+O\left(\frac{1}{n^3}\right)\Big) $$ Now, replacing $$\ln (y_n)=\sqrt{\frac{1}{n}} \left(1-\frac{1}{2} \ln \left(\frac{1}{n}\right)\right)+\frac{1}{8} \left(\frac{1}{n}\right)^{3/2} \ln \left(\frac{1}{n}\right)+O\left(\frac{1}{n^{5/2}}\right)$$ Now, using $y_n=e^{\ln(y_n)}$ and Taylor series again $$y_n=1+\sqrt{\frac{1}{n}} \left(1-\frac{1}{2} \log \left(\frac{1}{n}\right)\right)+O\left(\frac{1}{n}\right)$$ which shows the limit and also how it is approached.

For illustartion purposes, let us use $n=10000$ (this is far away from infinity). The rigorous calculation would give $y_n\approx 1.05765$ while the above formula would lead to $\approx 1.05605$.


Note that $$ \begin{align} 1\le\frac{(n+1)^{\sqrt{n+1}}}{n^{\sqrt{n}}} &=\left(1+\frac1n\right)^{\sqrt{n}}(n+1)^{\sqrt{n+1}-\sqrt{n}}\\ &=\left(1+\frac1n\right)^{\large\frac{n}{\sqrt{n}}} (n+1)^{\large\frac1{\sqrt{n+1}+\sqrt{n}}}\\ &\le e^{\large\frac1{\sqrt{n}}} \left(\sqrt{n+1}^{\frac1{\sqrt{n+1}}}\right)^2 \end{align} $$ The Squeeze Theorem then says that $$ \lim_{n\to\infty}\frac{(n+1)^{\sqrt{n+1}}}{n^{\sqrt{n}}}=1 $$

  • $\begingroup$ To see that $\left(\sqrt{n+1}^{\frac1{\sqrt{n+1}}}\right)^2 \to 0$ we can apply $\lim\limits_{n\to\infty} n^{1/n} =1$, right? Or, more precisely, $\lim\limits_{x\to\infty} x^{1/x} =1$. (This was shown here and in many other posts.) Or is there something more straightforward? $\endgroup$ – Martin Sleziak May 5 '16 at 7:17
  • 2
    $\begingroup$ Indeed, I was thinking of $\lim\limits_{x\to\infty}x^{1/x}=1$. If there is something more straightforward, I would be interested to see it. $\endgroup$ – robjohn May 5 '16 at 7:52

We present an approach here that relies only on a standard inequality and the squeeze theorem. To that end, we proceed.

First, note that we can write the limit of interest as

$$\lim_{n\to \infty}\left(\frac{(n+1)^{\sqrt{n+1}}}{n^\sqrt{n}}\right)=\lim_{n\to \infty}e^{\sqrt{n+1}\log(n+1)-\sqrt{n}\log(n)} \tag 1$$

Next, we analyze the exponent on the right-hand side of $(1)$.

Using the identity $\log(n+1)=\log(n)+\log\left(1+\frac1n\right)$, the exponent becomes

$$\begin{align} \sqrt{n+1}\log(n+1)-\sqrt{n}\log(n)&=\left(\sqrt{n+1}-\sqrt{n}\right)\log(n)+\sqrt{n+1}\log\left(1+\frac1n\right)\\\\ &=\frac{\log(n)}{\sqrt{n+1}+\sqrt{n}}+\sqrt{n+1}\log\left(1+\frac1n\right) \tag 2\\\\ \end{align}$$

Then, since for any $\alpha>0$, $\log(n)\le \frac{n^\alpha}{\alpha}$, we find that the term of interest satisfies the inequalities

$$0\le\frac{\log(n)}{\sqrt{n+1}+\sqrt{n}}+\sqrt{n+1}\log\left(1+\frac1n\right)\le \frac2{n^{1/4}}+\frac2{\sqrt{n}} \tag 3$$

Applying the squeeze theorem to $(3)$ yields

$$\lim_{n\to \infty} \left(\sqrt{n+1}\log(n+1)-\sqrt{n}\log(n)\right)=0 \tag 4$$

whence using $(4)$ in $(1)$, we find the coveted limit

$$\bbox[5px,border:2px solid #C0A000]{\lim_{n\to \infty}\frac{(n+1)^{\sqrt{n+1}}}{n^\sqrt{n}}=1}$$


Note $1$

In this note, we show that the logarithm function satisfies the inequality $\log(n)\le \frac{n^\alpha}{\alpha}$ for any $\alpha >0$. In THIS ANSWER, I showed using only the limit definition of the exponential function along with Bernoulli's Inequality that the logarithm function satisfies the inequalities

$$\frac{x-1}{x}\le\log(x)\le x-1<x \tag{N1}$$

for $x>0$. Then, using $\log(n^\alpha)=\alpha \log(n)$ in $(N1)$ with $x=n^\alpha$, we find

$$\log(n)\le \frac{n^\alpha -1}{\alpha}<\frac{n^\alpha}{\alpha} \tag {N2}$$

Note $2$

In this note, we show that $0\le \frac{\log(n)}{\sqrt{n+1}+\sqrt{n}}\le \frac{2}{n^{1/4}}$ for $n\ge 1$. The left-hand side inequality is trivial. For the right-hand side inequality we use $(N2)$ with $\alpha =1/4$.

Then, we see that $\log(n)\le 4n^{1/4}$. Putting that result together with the inequality $\frac{1}{\sqrt{n+1}+\sqrt{n}}\le \frac{1}{2\sqrt{n}}$, we obtain

$$0\le \frac{\log(n)}{\sqrt{n+1}+\sqrt{n}}\le \frac{2}{n^{1/4}}$$

as was to be shown.

Note $3$

In this note, we show $0\le \sqrt{n+1}\log\left(1+\frac1n\right)\le \frac2{\sqrt{n}}$, for $n\ge 1$. The left-hand side inequality is trivial. For the right-hand side inequality we use $(N1)$ with $x=1+\frac1n$.

Then, we see that $\log\left(1+\frac1n\right)\le \frac1n$. Putting that result together with $\sqrt{n+1}\le 2\sqrt{n}$, we obtain

$$0\le \sqrt{n+1}\log\left(1+\frac1n\right)\le \frac2{\sqrt{n}}$$

as was to be shown.

  • 1
    $\begingroup$ I didn't not understand the inequality clearly in $(3)$. But rest is good. I am trying to get around it. $\endgroup$ – Kushal Bhuyan May 5 '16 at 4:58
  • 1
    $\begingroup$ @Quintic Thank you! I have added some NOTES, one of which embeds the link to a solution that you might find useful. -Mark $\endgroup$ – Mark Viola May 5 '16 at 17:23
  • 1
    $\begingroup$ Thank you mark. Now it's all clear. NOTES are really good. $\endgroup$ – Kushal Bhuyan May 6 '16 at 1:49

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.